2001
DOI: 10.1086/320123
|View full text |Cite
|
Sign up to set email alerts
|

Recent Origin and Spread of a Common Lithuanian Mutation, G197del LDLR, Causing Familial Hypercholesterolemia: Positive Selection Is Not Always Necessary to Account for Disease Incidence among Ashkenazi Jews

Abstract: G197del is the most prevalent LDL receptor (LDLR) mutation causing familial hypercholesterolemia (FH) in Ashkenazi Jew (AJ) individuals. The purpose of this study was to determine the origin, age, and population distribution of G197del, as well as to explore environmental and genetic effects on disease expression. Index cases from Israel (n=46), South Africa (n=24), Russia (n=7), The Netherlands (n=1), and the United States (n=1) were enlisted. All trace their ancestry to Lithuania. A highly conserved haplotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 63 publications
4
31
0
1
Order By: Relevance
“…Figure 4c contrasts the Ashkenazi Jewish mismatch distribution with that of the Druze, a Near Eastern population with low effective size. 26 The Druze t of 4.6 is similar to that of the Ashkenazi Jews, again suggesting a period of shared growth. However, the Druze show an increase in f 0 , but not f 1 , as do the Ashkenazi Jewish populations.…”
Section: Mismatch Distributionsmentioning
confidence: 80%
See 3 more Smart Citations
“…Figure 4c contrasts the Ashkenazi Jewish mismatch distribution with that of the Druze, a Near Eastern population with low effective size. 26 The Druze t of 4.6 is similar to that of the Ashkenazi Jews, again suggesting a period of shared growth. However, the Druze show an increase in f 0 , but not f 1 , as do the Ashkenazi Jewish populations.…”
Section: Mismatch Distributionsmentioning
confidence: 80%
“…The higher dispersion of Near Eastern relative to European populations in the plot could be the result of stronger genetic drift in the Bedouins and Druze, two populations with small effective sizes. 26 Although not readily apparent in the MDS plot, AMOVA analysis (results not shown) indicated that Ashkenazi populations as a whole are genetically more similar to Near Eastern non-Jewish populations than to European non-Jewish populations. Table 1 reports HVS-1 haplotype diversity (h) and nucleotide diversity (p) values for our Ashkenazi samples, as well as for 10 European non-Jewish populations from similar geographic regions and five Near Eastern non-Jewish populations.…”
Section: Multidimensional Scaling (Mds) and Genetic Distances Betweenmentioning
confidence: 86%
See 2 more Smart Citations
“…La classe et le type de mutations sont reconnus pour avoir une influence sur les phénotypes de THF, leur impact sur le développement de MCA a été largement étudié (45, [55][56][57]. Les 920 mutations du gène du LDLR peuvent être divisées en cinq classes, selon l'effet qu'elles exercent sur l'expression de la protéine (Tableau 3).…”
Section: Les Mutations Dans Le Gène Du Ldlrunclassified